ROBOT PENCARI ALAMAT MENGGUNAKAN WARNA - Al Kausar; Venny Novita Sari (Jurnal Media Infotama, 2014)
The problem of the research is to design a robot that can search for an address by 4 colors (red, green, blue and black). The software used includes operating systems, programming languages and software pengelolah data. The operating sys-tem is Microsoft Windows XP3 is used as the operating system. The programming language used is Basic Programming Language - Bascom AVR, Delphi 7. The test is done by testing the search robots address by color goes according to plan, namely when given berintah then the sensor will look for the red color on the track and will send information to the microcontroller which direction the next track will give the command the robot to turn towards red and road.Keywords: Sensors, Color and Microcontroller